Contributory factors to soil spatial variability in an ultisol 1. Burning vegetation residues in heaps during land clearing - Hulugalle, N.R. (Informa UK Limited, 1992)
The effect of burning vegetation residues in heaps following in situprimary burning (not in heaps) during land clearing on soil properties was studied in a Typic Kandiudult in Southem Cameroon. Burning in heaps resulted in very poor or absence of plant growth during the following season. In relation to sites where burning was limited to primary burning, bulk density, penetrometer resistance, mean weight diameter of soil aggregates, pH, Bray‐l‐P, exchangeable Ca, K, and Na, and effective CEC, and soil temperatures on warm, sunny days were greater, and organic C, total N and total acidity were lower in the topsoil of sites where burning took place in heaps. The more compacted nature of the soil in such sites predisposes them to localized accelerated runoff and erosion. In general, subsoil physical and chemical properties were unaffected by burning in heaps, except for exchaneable K and Na which were greater. The absence of or poor plant growth in sites where burning occurred in heaps was attributed primarily to an imbalance in soil micronutrient availability induced by the rapid increase in pH.